Impact of maritime traffic and whale‐watching on apparent survival of bottlenose dolphins in the Strait of Gibraltar. Issue 5 (12th February 2020) - Tenan, Simone; Hernández, Noelia; Fearnbach, Holly; de Stephanis, Renaud; Verborgh, Philippe; Oro, Daniel
Abstract: The Strait of Gibraltar is an important habitat for cetaceans due to its high marine productivity. However, it is also the second most navigated channel in the world, subjecting cetaceans to a high level of vessel traffic, including an established whale‐watching fleet. Both maritime traffic and whale‐watching activities have been shown to impact the behaviour of cetaceans, but little is known about their impact on the demography and dynamics of cetacean populations. The aim of this study was to evaluate the impacts of both ferry traffic and whale‐watching vessels on the apparent survival probability of a bottlenose dolphin ( Tursiops truncatus ) population that occurs in the Strait. A Bayesian hierarchical mark–recapture modelling approach was applied to 8 years of photo‐identification data (2002–2009). Apparent annual survival probability was negatively correlated with ferry traffic, which explained >70% of temporal variation in survival, in contrast to whale‐watching, the effect of which was almost negligible. Despite these results, other natural and human‐related factors are likely to drive apparent survival in the study area. Abundance increased between 2002 and 2005, and then decreased between 2006 and 2009, while local per‐capita recruitment decreased from 2004 until the end of the study period. These shifts correlated temporally with the construction of a large harbour on the Moroccan coast, which increased maritime traffic significantly, including a 40% increase in ferry traffic that regularly transited the Strait. These results highlight the need to better understand the impact of maritime traffic on the demography of the dolphin population in the Strait, in order to implement evidence‐based conservation regulations in a region of high cetacean occurrence.